Scaling of immune responses against intracellular bacterial infection. (15th September 2014) - Abdullah, Zeinab; Knolle, Percy A
<x xml:space="preserve">Abstract</x> Percy Knolle and Zeinab Abdullah discuss how pattern recognition receptors and signaling pathways contribute to the scaling of immune responses against intracellular bacterial infection. <boxed-text content-type="graphic" id="embj201489055-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>